2004
DOI: 10.1007/s00705-004-0405-9
|View full text |Cite
|
Sign up to set email alerts
|

The enhanced virulence of very virulent infectious bursal disease virus is partly determined by its B-segment

Abstract: Summary. There is a remarkable difference in virulence of infectious bursal disease virus (IBDV) strains ranging from sub-clinical infections for serotype 2 and cell culture adapted serotype 1 strains, to 100% mortality for very virulent serotype 1 strains in young SPF chickens. It is known that cell culture adaptation related attenuation is determined by distinct mutations in the hypervariable region of the VP2 outer capsid protein, encoded on the A-segment. Amino acid mutations in the hypervariable VP2 regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 17 publications
6
39
1
2
Order By: Relevance
“…A number of reports have demonstrated the drastic effects of mutations of VP2 residues on attenuation of the virulence of vvIBDV (3,43); these residues were proposed to be related to the protein's receptor binding efficiency (5), but they are not the sole determinants of virulence (2). On the other hand, VP1 was also demonstrated to be a determinant of virulence in vivo, possibly by altering the replication efficiency (1,26). A recent study reported the isolation of a naturally reassorted IBDV with genome segment A of very virulent origin but genome segment B of non-very virulent origin; this isolate showed significantly reduced pathogenicity compared with typical vvIBDVs (25), demonstrating that the determinants on genome segment A may not be enough to induce the hypervirulence of typical vvIBDVs.…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports have demonstrated the drastic effects of mutations of VP2 residues on attenuation of the virulence of vvIBDV (3,43); these residues were proposed to be related to the protein's receptor binding efficiency (5), but they are not the sole determinants of virulence (2). On the other hand, VP1 was also demonstrated to be a determinant of virulence in vivo, possibly by altering the replication efficiency (1,26). A recent study reported the isolation of a naturally reassorted IBDV with genome segment A of very virulent origin but genome segment B of non-very virulent origin; this isolate showed significantly reduced pathogenicity compared with typical vvIBDVs (25), demonstrating that the determinants on genome segment A may not be enough to induce the hypervirulence of typical vvIBDVs.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting viruses proved to be attenuated for chickens (34,35), but reversion mutations were observed upon passage in chickens and could restore virulence (36). VP2 is, however, unlikely to be the only factor for virulence: laboratory-engineered reassortant viruses derived from vvIBDV exhibited delayed replication in the bursa (37) or failed to induce morbidity and mortality (31) unless they also had a typical vvIBDV-related segment B. This observation is consistent with the phylogeny-based hypothesis that both genome segments may be involved in the emergence of vvIBDV (38,39).…”
Section: Nfectious Bursal Disease Virus (Ibdv) Of Chickens (Gallus mentioning
confidence: 99%
“…Molecular characterization of IBDV has been based mainly on the analysis of the sequence of the variable region of VP2. However, there is evidence suggesting that VP2 is not the only protein responsible for pathogenicity of IBDV; other viral proteins may contribute to enhance the pathogenicity, particularly VP1 [30,36]. In addition to this, it has been shown that different vvIBDVs form a tight cluster, quite separate from other IBDV strains, when segment B is analyzed, which justifies the characterization of IBDV strains based on both genomic segments [37], particularly because it has been noted that it is possible for IBDV to undergo genetic reassortment, which can play an important role in the evolution of these viruses [38][39][40].…”
Section: Introductionmentioning
confidence: 99%